Neuromyelitis optica-IgG (aquaporin-4) autoantibodies in immune mediated optic neuritis. Issue 1 (17th December 2009) - Petzold, A; Pittock, S; Lennon, V; Maggiore, C; Weinshenker, B G; Plant, G T
Abstract : The clinical course of immune mediated optic neuritis (ON) will depend on the specific underlying inflammatory disease. These disorders have traditionally been classified according to clinical and MRI findings. Aquaporin-4 (AQP4) autoantibodies (neuromyelitis optica-IgG (NMO-IgG)) may have diagnostic and prognostic value in patients who present with isolated ON. In this prospective study, NMO-IgG was evaluated in 114 patients with ON in the following contexts: neuromyelitis optica (NMO), multiple sclerosis (MSON), chronic relapsing inflammatory ON (CRION), relapsing isolated ON (RION) and single isolated ON (SION). The proportion seropositive was 56% for NMO (n = 9), 0% for MSON (n = 28) and 5% for the remaining diagnostic categories (CRION (n = 19), RION (n = 17) and SION (n = 41)). Testing for NMO-IgG in patients with recurrent or severe ON who lack convincing evidence of MS may identify patients who would benefit from immunosuppression rather than MS directed immunomodulatory therapies.